THE FEATURES OF INFLATION IN RUSSIA - L. D. Efanova; S. A. Shmukler (Вестник университета, 2019)
The objective of the report is to determine the features of inflation and the major aspects of anti-inflationary policy. The report considers the factors that lead to inflation and its characteristics. The most effective regime, promoting domestic price stability has been defined and substantiated. The statistical information has been analysed by the inflation rate in Russia in the last decade. The report has determined the relationship between inflation and economic cycles and it outlined the key issues of overcoming inflation in Russia.